The Central Role of Inflammation Associated with Checkpoint Inhibitor Treatments. (17th October 2018) - Vajaitu, Cristina; Draghici, Carmen Cristina; Solomon, Iulia; Lisievici, Cristina Victoria; Popa, Alexandra Victoria; Lupu, Mihai; Caruntu, Constantin; Constantin, Maria Magdalena; Voiculescu, Vlad Mihai
Abstract : An important function of the immune system is its ability to differentiate between healthy cells in the organism and "foreign" cells, allowing the latest to be attacked and the first ones to be conserved. The most important molecules in this process are considered to be checkpoint inhibitors. This review is focused on the association between cancer and inflammation, underlying the mechanisms of action of monoclonal antibodies that are targeting checkpoint inhibitors: ipilimumab against cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) and pembrolizumab and nivolumab against programmed cell death protein 1 (PD-1), their indications for treatment, and side effects. Presence of antibodies against checkpoint inhibitors shows promising results in the clinical trials in patients with types of cancer difficult to treat until now such as melanoma, non-small-cell lung cancer (NSCLC), and renal cell carcinoma, offering an increase in the overall survival rate, response rate, and progression-free rate. Resistance is now observed to emerge in patients treated with this therapy, showing the need for more studies in order to design a biomarker that will predict the type of response to immunotherapy.